Identifying the critical success factors of an in-flight connectivity project implementation - Daruğa, Duygu Selen (Graduate School, 2024)
Remaining connected at all times is becoming increasingly important in today's world, where communication plays a central role in lives of people and staying connected becomes a necessity rather than a luxury. This need for constant connection extends beyond the ground to include travel periods on the sea, railways and airplanes. As a result, one of the critical needs emerging in the commercial aviation industry is in-flight connectivity (IFC). The rising demand among airline passengers has led airlines to launch projects and equip their aircraft with IFC equipment to provide connectivity services to their customers and meet the demand. These projects can be undertaken by companies operating in different fields in the aviation industry, from production to communication. In addition to the companies that are already in this business, companies entering the market from certain segments of aviation continue to shape the sector. While new entrants to the industry are often not completely unfamiliar with the concept of in-flight connectivity, they may also lack experience in managing an end-to-end IFC project. Considered as corporate entrepreneurship projects, IFC projects face a multitude of complex challenges including but not limited to operational and technological issues. The diversity of players in the industry, various available and 'near future' technological infrastructure options, the effect of national and international regulators complicates IFC projects for decision makers. As much as external factors, the internal factors of both the airline and the IFC provider have an impact on project success. In this study, the factors affecting the success of an in-flight connectivity project were examined and these critical factors were identified and analysed under 5 main headings which are determined with in-depth interview with experts: technological, regulatory, operational, managerial and user-oriented elements. The identified key success factors were analysed with the fuzzy cognitive mapping modelling approach. Understanding and internalizing these key success factors is necessary to maximize the benefit in in-flight connection projects and ensure continued success. In addition, the response of the model to some possible situations was examined through scenario analysis.
Bir uçak içi bağlantı projesinin uygulanmasında kritik başarı faktörlerinin belirlenmesi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2024
Keywords: fuzzy logic; bulanık mantık